1980
DOI: 10.1139/m80-103
|View full text |Cite
|
Sign up to set email alerts
|

A streptomycete antagonist to Phellinus weirii, Fomes annosus, and Phytophthora cinnamomi

Abstract: An actinomycete isolated from the rhizoplane of nitrogen-fixing nodules of Ceanothus velutinus was identified as a variety of Streptomyces griseoloalbus. Streptomyces griseoloalbus is a strong antagonist to three destructive root pathogens, Phellinus weirii, Fomes annosus, and Phytophthora cinnamomi, inhibiting all three on several culture media and preventing establishment of F. annosus on hemlock wood disks. The stability and longevity of the antimicrobial substance produced by it, its consistent effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1982
1982
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…A number of investigations have reported antagonism of root-pathogenic fungi by soil actinomycetes (6,40) and that especially streptomycetes are a rich source of antifungal compounds (20).…”
mentioning
confidence: 99%
“…A number of investigations have reported antagonism of root-pathogenic fungi by soil actinomycetes (6,40) and that especially streptomycetes are a rich source of antifungal compounds (20).…”
mentioning
confidence: 99%
“…stands that were asymptomatic of Armillaria, but they did not elaborate on the abilities of these bacteria to inhibit Armillaria. HUTCHINS (1980) isolated a species of Bacillus that inhibited Armillaria from alder ( A h u s sp.) forest soil.…”
Section: Introductionmentioning
confidence: 99%
“…Although the API ZYM system was able to differenti- Numerous investigators have reported antagonistic effects of actinomycetes to a variety of bacteria and fungi both in and out of the rhizospheres of grasses and other plants (Strzelczyk 1961;Rice 1964;Rose et al 1980). The inhibition is thought to be due primarily to an antimicrobial substance or antibiotic produced by the actinomycetes (Ballesta and Alexander 1972).…”
mentioning
confidence: 99%
“…Much recent work has been done on antagonistic effects of actinomycetes against fungi (Rose et al 1980;Whaley and Boyle 1967) and on the bacterial genus Rhizobium (Pate1 1974). However, with the exception of some work on Azotobacter (Strzelczyk 1961;Pate1 and Brown 1969), little information is available on the antagonistic effects of actinomycetes against a variety of nonsymbiotic nitrogen-fixing bacteria from the rhizospheres of grasses.…”
mentioning
confidence: 99%